2020
DOI: 10.1038/s41591-020-0939-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct synovial tissue macrophage subsets regulate inflammation and remission in rheumatoid arthritis

Abstract: Treatment-refractory rheumatoid arthritis (RA) is a major clinical challenge. Drug-free remission is uncommon but provides proof-of-concept that articular immune-homeostasis can be reinstated. Here we identify active cellular and molecular mechanisms of sustained remission in RA. Single-cell transcriptomics (32,000 cells) identified phenotypic changes in synovial tissue macrophages (STM) spanning health, early/active RA, treatment-refractory/active RA, and RA in sustained remission. Each clinical state is char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
535
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 409 publications
(573 citation statements)
references
References 63 publications
36
535
1
1
Order By: Relevance
“…The severity of COVID-19 is attributable to immune dysregulation, abnormal blood clotting and tissue disruption, particularly implicating pro-inflammatory innate immunity 1-3 . Interstitial lung disease and alveolitis is a co-morbidity of rheumatoid arthritis (RA) 4 , in which articular inflammation and disease remission are driven by distinct synovial tissue macrophage clusters 5 . Despite suggestive early data 2 6-10 there is a knowledge gap of how myeloid cell pathways mechanistically regulate severity or contribute to the resolution of COVID-19, hindering development of effective treatments 11-14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of COVID-19 is attributable to immune dysregulation, abnormal blood clotting and tissue disruption, particularly implicating pro-inflammatory innate immunity 1-3 . Interstitial lung disease and alveolitis is a co-morbidity of rheumatoid arthritis (RA) 4 , in which articular inflammation and disease remission are driven by distinct synovial tissue macrophage clusters 5 . Despite suggestive early data 2 6-10 there is a knowledge gap of how myeloid cell pathways mechanistically regulate severity or contribute to the resolution of COVID-19, hindering development of effective treatments 11-14 .…”
Section: Introductionmentioning
confidence: 99%
“…Their roles in the pathogenesis of severe COVID-19 have yet to be established. We recently identified similar macrophage diversity in synovial tissue (ST) of healthy donors and patients with active or remission rheumatoid arthritis (RA) 5 . Whilst RA is not a viral respiratory syndrome, it represents a pro-inflammatory cytokine-driven chronic articular condition often accompanied by cardiovascular and lung pathologies 4 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many RA patients suffer from periodic arthritic flares, but the mechanisms that promote and sustain bouts of joint inflammation remain poorly understood. Recent investigations suggest a contribution from circulating IgD + immature B lymphocytes and PRIME cells, as well as synovial macrophage populations (8,9). These novel observations are also consistent with our model of lymphatic dysfunction in RA flare 7, as: 1) the circulating IgD + B-cells may be the Bin cells that we observe within the lymphatic sinuses (20,21,35), 2) the circulating PDPN + PRIME cells may be lymphatic endothelial progenitors that are mobilized to repair damaged lymphatic vessels, and 3) the activated adherent macrophages in the lumen of degenerated PLVs (42) are likely from the afferent inflamed synovium (35,43).…”
Section: Discussionmentioning
confidence: 99%
“…Although autoimmune mechanisms underlie the development of RA, the pathways that trigger flare are not well understood, and alternative pathways may contribute to disease exacerbation (7). Although recent gene expression studies have identified potential roles of immature IgD + Bcells, circulating CD45 -/CD31 -/PDPN + pre-inflammatory mesenchymal (PRIME) cells, and synovial macrophages in RA flare (8,9), it is also possible that exacerbation of disease is due to the loss of protective mechanisms in the setting of chronic joint inflammation. One area of interest receiving increased attention in RA is the synovial lymphatic system and its dysfunction, based on animal models and clinical pilots, where the loss of lymphatic drainage of inflamed joints is strongly implicated in the onset of synovitis and disease progression (7,10,11).…”
Section: Introductionmentioning
confidence: 99%